Isostatic graphite and preparation process thereof
By using modified coke powder and modified binder in the preparation of isostatic graphite, combined with specific concentrated sulfuric acid treatment and segmented pressing processes, the performance instability of isostatic graphite in high temperature and high pressure environments is solved and the performance of isostatic graphite is unstable and The density uneven problem caused by the preparation process achieves high performance and low waste rate isostatic graphite.
Patent Information
- Application Number
- CN202411401380.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-09
- Publication Date
- 2025-01-07
AI Technical Summary
The existing isostatic graphite has unstable performance in high temperature and high pressure environments, and its application range is limited. The preparation process leads to uneven product volume density, which increases the scrap rate.
Using modified coke powder and modified binder, through specific preparation process flow, including concentrated sulfuric acid treatment, ultrasonic dispersion and segmented pressing, the ratio of graphite powder to graphene and the ratio of concentrated sulfuric acid solution is adjusted to form a high density , high-strength isostatic pressure graphite.
It improves the comprehensive performance of isostatic graphite, including high density, high thermal conductivity, high corrosion resistance and dimensional stability, reduces waste rate, broadens the application range, and maintains stability in complex environments.
Smart Images

Figure CN119263837A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of graphite, in particular to isostatically pressed graphite and a preparation process thereof. Background Art
[0002] With the continuous development of modern science and technology, the demand for new materials in various fields is also increasing. Among them, isostatic graphite, as a high-performance material, is widely used due to its unique physical and chemical properties.
[0003] Isostatic graphite is a new type of material pressed from high-purity graphite. Compared with conventional graphite, isostatic graphite products have a denser structure, excellent uniformity, excellent chemical corrosion resistance and good electrical conductivity. It can be used in many fields, and can be widely used in metallurgy, chemistry, electricity, aerospace and atomic energy industries.
[0004] In order to further improve the application field of isostatic graphite, the performance of isostatic graphite prepared by the prior art has been further improved, mainly by improving the isostatic graphite raw materials and the preparation process, so as to obtain isostatic graphite products with better performance.
[0005] Based on this, an isostatic graphite and a preparation process thereof are provided to solve the existing technical problems. Summary of the invention
[0006] The purpose of the present invention is to provide an isostatic graphite and a preparation process thereof to solve the deficiencies in the prior art.
[0007] The technical solution adopted by the present invention is as follows:
[0008] An isostatic graphite is prepared by including the following components by weight: 10-16 parts of asphalt, 12-14 parts of modified coke powder, 20-28 parts of graphite powder, 5-7 parts of graphene, 5-8 parts of modified binder, and 3-6 parts of water;
[0009] The weight ratio of graphite powder to graphene is 4:1.
[0010] As a further technical solution: the method for preparing the modified coke powder is:
[0011] First, add the coke powder to the concentrated sulfuric acid solution, adjust the temperature to 80°C, keep the temperature and stir for 2 hours, then filter, wash with water until neutral, and dry to obtain the pretreated coke powder;
[0012] Among them, the drying temperature is 75°C and the time is 1 hour;
[0013] The pretreated coke powder, surfactant and solvent were sequentially added into a mixer, stirred for 2 hours in a water bath at 80°C, and then subjected to ultrasonic dispersion to obtain a dispersion liquid;
[0014] The dispersion was kept warm and allowed to stand for 24 hours to obtain an aged dispersion;
[0015] The aged dispersion liquid is filtered, washed to neutrality, and dried to constant weight to obtain modified coke powder;
[0016] The drying temperature was 55°C and the drying time was 2 hours.
[0017] As a further technical solution: the mixing ratio of the coke powder and the concentrated sulfuric acid solution is 5g:80-90mL;
[0018] The mass fraction of the concentrated sulfuric acid solution is 70%
[0019] As a further technical solution: the mixing ratio of the pretreated coke powder, surfactant and solvent is 30-40g:3-5g:300mL.
[0020] As a further technical solution: the surfactant is sodium dodecylbenzene sulfonate;
[0021] The solvent is water.
[0022] As a further technical solution: the preparation method of the modified binder is:
[0023] Adding starch to water and beating it at high speed to obtain starch slurry;
[0024] Adding sodium alginate to the starch slurry and continuing stirring for 2 hours to obtain a composite starch slurry;
[0025] The temperature of the composite starch slurry was adjusted to 85° C. and stirred for 4 hours to obtain the modified binder.
[0026] As a further technical solution: the starch is soybean starch;
[0027] The starch and water mixing mass ratio is 1:5;
[0028] The high-speed beating speed is 4000r / min;
[0029] The mixing ratio of the starch slurry and sodium alginate is 120 mL:5 g.
[0030] A method for preparing isostatically pressed graphite comprises the following steps:
[0031] S1: weighing the raw material components according to their weight parts: asphalt, modified coke powder, graphite powder, graphene, modified binder, and water;
[0032] S2: adding modified coke powder, graphite powder, graphene and water to a mixer in sequence, stirring and mixing for 20 minutes, and then adding asphalt and modified binder respectively, and continuing to stir for 30 minutes to obtain a mixed slurry;
[0033] S3: adding the mixed slurry into a mold, pressing, and then drying to obtain a blank;
[0034] S4 adds the blank to the isostatic pressing die, adjusts the pressure to 300-330 MPa, maintains for 40 min, then adjusts the pressure to 450-460 MPa, continues to maintain for 30 min, and finally adjusts the pressure to 500-520 MPa, maintains for 25 min, to obtain a pressed material;
[0035] S5 graphitizes the pressed material, cools it, and obtains isostatic graphite.
[0036] As a further technical solution: the drying temperature is 200° C. and the drying time is 30 minutes.
[0037] As a further technical solution: the graphitization treatment is carried out at 2500-2550°C for 30-35 hours;
[0038] The graphitization heating rate is 10°C / s.
[0039] Beneficial effects:
[0040] The isostatically pressed graphite prepared by the invention has the characteristics of high density, high strength, high thermal conductivity, high corrosion resistance, good dimensional stability and the like.
[0041] The present invention makes corresponding improvements to the raw materials and preparation process of isostatic graphite in the prior art, thereby greatly improving its comprehensive performance, being able to maintain high stability under high temperature and high pressure environments, thereby further broadening the application range of the prepared isostatic graphite.
[0042] The present invention introduces modified coke powder so that the prepared isostatic graphite has the characteristic of isotropy, which shows that the excellent properties of the isostatic graphite prepared by the present invention will not be affected by factors such as gas size and shape, and can adapt to various complex environments.
[0043] The present invention adopts a segmented pressing process in the preparation process, which can effectively avoid the disadvantage of uneven product volume density caused by the traditional molding process, and can greatly reduce the probability of product cracking, thereby effectively reducing the scrap rate and improving the yield rate. BRIEF DESCRIPTION OF THE DRAWINGS
[0044] Figure 1The present invention is a flow chart for the preparation of isostatic graphite. DETAILED DESCRIPTION
[0045] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0046] Example 1
[0047] A method for preparing isostatically pressed graphite comprises the following steps:
[0048] S1 weighed the raw material components according to their weight: 10 parts of asphalt, 12 parts of modified coke powder, 20 parts of graphite powder, 5 parts of graphene, 5 parts of modified binder, and 3 parts of water;
[0049] The weight ratio of graphite powder to graphene is 4:1.
[0050] The preparation method of modified coke powder is as follows:
[0051] First, add the coke powder to the concentrated sulfuric acid solution, adjust the temperature to 80°C, keep the temperature and stir for 2 hours, then filter, wash with water until neutral, and dry to obtain the pretreated coke powder;
[0052] Among them, the drying temperature is 75°C and the time is 1 hour;
[0053] The pretreated coke powder, surfactant and solvent were sequentially added into a mixer, stirred for 2 hours in a water bath at 80°C, and then subjected to ultrasonic dispersion to obtain a dispersion liquid;
[0054] The dispersion was kept warm and allowed to stand for 24 hours to obtain an aged dispersion;
[0055] The aged dispersion liquid is filtered, washed to neutrality, and dried to constant weight to obtain modified coke powder;
[0056] The drying temperature was 55°C and the drying time was 2 hours.
[0057] The mixing ratio of coke powder and concentrated sulfuric acid solution is 5g:80mL;
[0058] The mass fraction of the concentrated sulfuric acid solution is 70%
[0059] The mixing ratio of pretreated coke powder, surfactant and solvent is 30g:3g:300mL.
[0060] The surfactant is sodium dodecylbenzene sulfonate;
[0061] The solvent is water.
[0062] The preparation method of the modified binder is:
[0063] Adding starch to water and beating it at high speed to obtain starch slurry;
[0064] Adding sodium alginate to the starch slurry and continuing stirring for 2 hours to obtain a composite starch slurry;
[0065] The temperature of the composite starch slurry was adjusted to 85° C. and stirred for 4 hours to obtain the modified binder.
[0066] The starch is soybean starch;
[0067] The starch and water mixing mass ratio is 1:5;
[0068] The high-speed beating speed is 4000r / min;
[0069] The mixing ratio of the starch slurry and sodium alginate is 120 mL:5 g.
[0070] S2: adding modified coke powder, graphite powder, graphene and water to a mixer in sequence, stirring and mixing for 20 minutes, and then adding asphalt and modified binder respectively, and continuing to stir for 30 minutes to obtain a mixed slurry;
[0071] S3: adding the mixed slurry into a mold, pressing, and then drying to obtain a blank;
[0072] S4 adds the blank into the isostatic pressing die, adjusts the pressure to 300 MPa, maintains it for 40 min, then adjusts the pressure to 450 MPa, continues to maintain it for 30 min, and finally adjusts the pressure to 500 MPa, maintains it for 25 min, to obtain the pressed material;
[0073] S5 graphitizes the pressed material, cools it, and obtains isostatic graphite.
[0074] The drying temperature is 200°C and the time is 30 minutes.
[0075] The graphitization treatment was carried out at 2500°C for 30 hours;
[0076] The graphitization heating rate is 10℃ / s.
[0077] Example 2
[0078] A method for preparing isostatically pressed graphite comprises the following steps:
[0079] S1 weighed the raw material components according to their weight: 12 parts of asphalt, 13 parts of modified coke powder, 24 parts of graphite powder, 6 parts of graphene, 6 parts of modified binder, and 4 parts of water;
[0080] The weight ratio of graphite powder to graphene is 4:1.
[0081] The preparation method of modified coke powder is as follows:
[0082] First, add the coke powder to the concentrated sulfuric acid solution, adjust the temperature to 80°C, keep the temperature and stir for 2 hours, then filter, wash with water until neutral, and dry to obtain the pretreated coke powder;
[0083] Among them, the drying temperature is 75°C and the time is 1 hour;
[0084] The pretreated coke powder, surfactant and solvent were sequentially added into a mixer, stirred for 2 hours in a water bath at 80°C, and then subjected to ultrasonic dispersion to obtain a dispersion liquid;
[0085] The dispersion was kept warm and allowed to stand for 24 hours to obtain an aged dispersion;
[0086] The aged dispersion liquid is filtered, washed to neutrality, and dried to constant weight to obtain modified coke powder;
[0087] The drying temperature was 55°C and the drying time was 2 hours.
[0088] The mixing ratio of coke powder and concentrated sulfuric acid solution is 5g:85mL;
[0089] The mass fraction of the concentrated sulfuric acid solution is 70%
[0090] The mixing ratio of pretreated coke powder, surfactant and solvent is 32g:4g:300mL.
[0091] The surfactant is sodium dodecylbenzene sulfonate;
[0092] The solvent is water.
[0093] The preparation method of the modified binder is:
[0094] Adding starch to water and beating it at high speed to obtain starch slurry;
[0095] Adding sodium alginate to the starch slurry and continuing stirring for 2 hours to obtain a composite starch slurry;
[0096] The temperature of the composite starch slurry was adjusted to 85° C. and stirred for 4 hours to obtain the modified binder.
[0097] The starch is soybean starch;
[0098] The starch and water mixing mass ratio is 1:5;
[0099] The high-speed beating speed is 4000r / min;
[0100] The mixing ratio of the starch slurry and sodium alginate is 120 mL:5 g.
[0101] S2: adding modified coke powder, graphite powder, graphene and water to a mixer in sequence, stirring and mixing for 20 minutes, and then adding asphalt and modified binder respectively, and continuing to stir for 30 minutes to obtain a mixed slurry;
[0102] S3: adding the mixed slurry into a mold, pressing, and then drying to obtain a blank;
[0103] S4 adds the blank to the isostatic pressing die, adjusts the pressure to 310 MPa, maintains it for 40 min, then adjusts the pressure to 455 MPa, continues to maintain it for 30 min, and finally adjusts the pressure to 510 MPa, maintains it for 25 min, to obtain the pressed material;
[0104] S5 graphitizes the pressed material, cools it, and obtains isostatic graphite.
[0105] The drying temperature is 200°C and the time is 30 minutes.
[0106] The graphitization treatment was carried out at 2530°C for 32 hours;
[0107] The graphitization heating rate is 10℃ / s.
[0108] Example 3
[0109] A method for preparing isostatically pressed graphite comprises the following steps:
[0110] S1 weighed the raw material components according to their weight: 13 parts of asphalt, 13 parts of modified coke powder, 25 parts of graphite powder, 6.25 parts of graphene, 6 parts of modified binder, and 5 parts of water;
[0111] The weight ratio of graphite powder to graphene is 4:1.
[0112] The preparation method of modified coke powder is as follows:
[0113] First, add the coke powder to the concentrated sulfuric acid solution, adjust the temperature to 80°C, keep the temperature and stir for 2 hours, then filter, wash with water until neutral, and dry to obtain the pretreated coke powder;
[0114] Among them, the drying temperature is 75°C and the time is 1 hour;
[0115] The pretreated coke powder, surfactant and solvent were sequentially added into a mixer, stirred for 2 hours in a water bath at 80°C, and then subjected to ultrasonic dispersion to obtain a dispersion liquid;
[0116] The dispersion was kept warm and allowed to stand for 24 hours to obtain an aged dispersion;
[0117] The aged dispersion liquid is filtered, washed to neutrality, and dried to constant weight to obtain modified coke powder;
[0118] The drying temperature was 55°C and the drying time was 2 hours.
[0119] The mixing ratio of coke powder and concentrated sulfuric acid solution is 5g:82mL;
[0120] The mass fraction of the concentrated sulfuric acid solution is 70%
[0121] The mixing ratio of pretreated coke powder, surfactant and solvent is 38g:4g:300mL.
[0122] The surfactant is sodium dodecylbenzene sulfonate;
[0123] The solvent is water.
[0124] The preparation method of the modified binder is:
[0125] Adding starch to water and beating it at high speed to obtain starch slurry;
[0126] Adding sodium alginate to the starch slurry and continuing stirring for 2 hours to obtain a composite starch slurry;
[0127] The temperature of the composite starch slurry was adjusted to 85° C. and stirred for 4 hours to obtain the modified binder.
[0128] The starch is soybean starch;
[0129] The starch and water mixing mass ratio is 1:5;
[0130] The high-speed beating speed is 4000r / min;
[0131] The mixing ratio of the starch slurry and sodium alginate is 120 mL:5 g.
[0132] S2: adding modified coke powder, graphite powder, graphene and water to a mixer in sequence, stirring and mixing for 20 minutes, and then adding asphalt and modified binder respectively, and continuing to stir for 30 minutes to obtain a mixed slurry;
[0133] S3: adding the mixed slurry into a mold, pressing, and then drying to obtain a blank;
[0134] S4 adds the blank to the isostatic pressing die, adjusts the pressure to 305 MPa, maintains it for 40 min, then adjusts the pressure to 456 MPa, continues to maintain it for 30 min, and finally adjusts the pressure to 515 MPa, maintains it for 25 min, to obtain the pressed material;
[0135] S5 graphitizes the pressed material, cools it, and obtains isostatic graphite.
[0136] The drying temperature is 200°C and the time is 30 minutes.
[0137] The graphitization treatment was carried out at 2540°C for 33 hours;
[0138] The graphitization heating rate is 10°C / s.
[0139] Example 4
[0140] A method for preparing isostatically pressed graphite comprises the following steps:
[0141] S1 weighed the raw material components according to their weight: 14 parts of asphalt, 13 parts of modified coke powder, 25 parts of graphite powder, 6.25 parts of graphene, 6 parts of modified binder, and 5 parts of water;
[0142] The weight ratio of graphite powder to graphene is 4:1.
[0143] The preparation method of modified coke powder is as follows:
[0144] First, add the coke powder to the concentrated sulfuric acid solution, adjust the temperature to 80°C, keep the temperature and stir for 2 hours, then filter, wash with water until neutral, and dry to obtain the pretreated coke powder;
[0145] Among them, the drying temperature is 75°C and the time is 1 hour;
[0146] The pretreated coke powder, surfactant and solvent were sequentially added into a mixer, stirred for 2 hours in a water bath at 80°C, and then subjected to ultrasonic dispersion to obtain a dispersion liquid;
[0147] The dispersion was kept warm and allowed to stand for 24 hours to obtain an aged dispersion;
[0148] The aged dispersion liquid is filtered, washed to neutrality, and dried to constant weight to obtain modified coke powder;
[0149] The drying temperature was 55°C and the drying time was 2 hours.
[0150] The mixing ratio of coke powder and concentrated sulfuric acid solution is 5g:85mL;
[0151] The mass fraction of the concentrated sulfuric acid solution is 70%
[0152] The mixing ratio of pretreated coke powder, surfactant and solvent is 34g:4g:300mL.
[0153] The surfactant is sodium dodecylbenzene sulfonate;
[0154] The solvent is water.
[0155] The preparation method of the modified binder is:
[0156] Adding starch to water and beating it at high speed to obtain starch slurry;
[0157] Adding sodium alginate to the starch slurry and continuing stirring for 2 hours to obtain a composite starch slurry;
[0158] The temperature of the composite starch slurry was adjusted to 85° C. and stirred for 4 hours to obtain the modified binder.
[0159] The starch is soybean starch;
[0160] The starch and water mixing mass ratio is 1:5;
[0161] The high-speed beating speed is 4000r / min;
[0162] The mixing ratio of the starch slurry and sodium alginate is 120 mL:5 g.
[0163] S2: adding modified coke powder, graphite powder, graphene and water to a mixer in sequence, stirring and mixing for 20 minutes, and then adding asphalt and modified binder respectively, and continuing to stir for 30 minutes to obtain a mixed slurry;
[0164] S3: adding the mixed slurry into a mold, pressing, and then drying to obtain a blank;
[0165] S4 adds the blank to the isostatic pressing die, adjusts the pressure to 320 MPa, maintains it for 40 min, then adjusts the pressure to 452 MPa, continues to maintain it for 30 min, and finally adjusts the pressure to 516 MPa, maintains it for 25 min, to obtain the pressed material;
[0166] S5 graphitizes the pressed material, cools it, and obtains isostatic graphite.
[0167] The drying temperature is 200°C and the time is 30 minutes.
[0168] The graphitization treatment was carried out at 2540°C for 34 hours;
[0169] The graphitization heating rate is 10°C / s.
[0170] Example 5
[0171] A method for preparing isostatically pressed graphite comprises the following steps:
[0172] S1 weighed the raw material components according to their weight: 16 parts of asphalt, 14 parts of modified coke powder, 28 parts of graphite powder, 7 parts of graphene, 8 parts of modified binder, and 6 parts of water;
[0173] The weight ratio of graphite powder to graphene is 4:1.
[0174] The preparation method of modified coke powder is as follows:
[0175] First, add the coke powder to the concentrated sulfuric acid solution, adjust the temperature to 80°C, keep the temperature and stir for 2 hours, then filter, wash with water until neutral, and dry to obtain the pretreated coke powder;
[0176] Among them, the drying temperature is 75°C and the time is 1 hour;
[0177] The pretreated coke powder, surfactant and solvent were sequentially added into a mixer, stirred for 2 hours in a water bath at 80°C, and then subjected to ultrasonic dispersion to obtain a dispersion liquid;
[0178] The dispersion was kept warm and allowed to stand for 24 hours to obtain an aged dispersion;
[0179] The aged dispersion liquid is filtered, washed to neutrality, and dried to constant weight to obtain modified coke powder;
[0180] The drying temperature was 55°C and the drying time was 2 hours.
[0181] The mixing ratio of coke powder and concentrated sulfuric acid solution is 5g:90mL;
[0182] The mass fraction of the concentrated sulfuric acid solution is 70%
[0183] The mixing ratio of pretreated coke powder, surfactant and solvent is 40g:5g:300mL.
[0184] The surfactant is sodium dodecylbenzene sulfonate;
[0185] The solvent is water.
[0186] The preparation method of the modified binder is:
[0187] Adding starch to water and beating it at high speed to obtain starch slurry;
[0188] Adding sodium alginate to the starch slurry and continuing stirring for 2 hours to obtain a composite starch slurry;
[0189] The temperature of the composite starch slurry was adjusted to 85° C. and stirred for 4 hours to obtain the modified binder.
[0190] The starch is soybean starch;
[0191] The starch and water mixing mass ratio is 1:5;
[0192] The high-speed beating speed is 4000r / min;
[0193] The mixing ratio of the starch slurry and sodium alginate is 120 mL:5 g.
[0194] S2: adding modified coke powder, graphite powder, graphene and water to a mixer in sequence, stirring and mixing for 20 minutes, and then adding asphalt and modified binder respectively, and continuing to stir for 30 minutes to obtain a mixed slurry;
[0195] S3: adding the mixed slurry into a mold, pressing, and then drying to obtain a blank;
[0196] S4 adds the blank to the isostatic pressing die, adjusts the pressure to 330 MPa, maintains it for 40 min, then adjusts the pressure to 460 MPa, continues to maintain it for 30 min, and finally adjusts the pressure to 520 MPa, maintains it for 25 min, to obtain a pressed material;
[0197] S5 graphitizes the pressed material, cools it, and obtains isostatic graphite.
[0198] The drying temperature is 200°C and the time is 30 minutes.
[0199] The graphitization treatment was carried out at 2550°C for 35 hours;
[0200] The graphitization heating rate is 10°C / s.
[0201] Comparative Example 1:
[0202] The difference from Example 1 is that modified coke powder is not added, and the rest of the technical solutions remain unchanged.
[0203] Comparative Example 2
[0204] The difference from Example 1 is that no modified binder is added, and the rest of the technical solutions remain unchanged.
[0205] test:
[0206] The bulk density of the isostatically pressed graphite sample of the embodiment was tested according to GB / T24528-2009 "Determination of bulk density of carbon materials":
[0207] Table 1
[0208] <![CDATA[Volume density g / cm 3 > Example 1 1.89 Example 2 1.86 Example 3 1.92 Example 4 1.87 Example 5 1.90
[0209] It can be seen from Table 2 that the isostatic graphite prepared by the present invention has a higher bulk density and a higher hardness.
[0210] The flexural strength test was performed on the samples prepared by the process of the embodiment and the comparative example:
[0211] Among them, the flexural strength is tested with reference to GB / T3074.1-2021 "Determination method of flexural strength of carbon materials":
[0212] Table 2
[0213]
[0214]
[0215] It can be seen from Table 3 that the isostatic graphite prepared in the present invention has excellent flexural strength. The introduction of modified coke powder can significantly improve the flexural strength of the isostatic graphite.
[0216] The resistivity of the samples of the embodiment and the comparative example was tested:
[0217] Table 3
[0218] Resistivity μΩ·m Example 1 6.5 Example 2 6.3 Example 3 6.1 Example 4 6.3 Example 5 6.6 Comparative Example 1 7.4 Comparative Example 2 6.8
[0219] It can be seen from Table 3 that the isostatic graphite obtained in the present invention has a lower resistivity, indicating that it has excellent conductive properties.
[0220] The scrap rates of the finished products obtained in the embodiments and comparative examples were statistically analyzed, with 100 pieces in each group;
[0221] Table 4
[0222]
[0223]
[0224] It can be seen from Table 4 that the isostatic graphite prepared by the present invention has a lower scrap rate and a higher yield rate.
[0225] The above description is only a preferred embodiment of the present invention, but the present invention is not limited to the scope of implementation shown. Any changes made in accordance with the concept of the present invention, or modifications to equivalent embodiments with equivalent changes, which still do not exceed the spirit covered by the specification, should be within the protection scope of the present invention.
Claims
1. An isostatic graphite, characterized in that: The composition comprises the following components by weight: 10-16 parts of asphalt, 12-14 parts of modified coke powder, 20-28 parts of graphite powder, 5-7 parts of graphene, 5-8 parts of modified binder, and 3-6 parts of water; The weight ratio of graphite powder to graphene is 4:
1.
2. The isostatically pressed graphite according to claim 1, characterized in that: The modified coke powder preparation method is: First, add the coke powder to the concentrated sulfuric acid solution, adjust the temperature to 80°C, keep the temperature and stir for 2 hours, then filter, wash with water until neutral, and dry to obtain the pretreated coke powder; Among them, the drying temperature is 75°C and the time is 1 hour; The pretreated coke powder, surfactant and solvent were sequentially added into a mixer, stirred for 2 hours in a water bath at 80°C, and then subjected to ultrasonic dispersion to obtain a dispersion liquid; The dispersion was kept warm and allowed to stand for 24 hours to obtain an aged dispersion; The aged dispersion liquid is filtered, washed to neutrality, and dried to constant weight to obtain modified coke powder; The drying temperature was 55°C and the drying time was 2 hours.
3. The isostatically pressed graphite according to claim 2, characterized in that: The mixing ratio of the coke powder and the concentrated sulfuric acid solution is 5g:80-90mL; The mass fraction of the concentrated sulfuric acid solution is 70%.
4. The isostatically pressed graphite according to claim 3, characterized in that: The mixing ratio of the pretreated coke powder, surfactant and solvent is 30-40g:3-5g:300mL.
5. The isostatically pressed graphite according to claim 4, characterized in that: The surfactant is sodium dodecylbenzene sulfonate; The solvent is water.
6. The isostatically pressed graphite according to claim 1, characterized in that: The modified binder preparation method is: Adding starch to water and beating it at high speed to obtain starch slurry; Adding sodium alginate to the starch slurry and continuing stirring for 2 hours to obtain a composite starch slurry; The temperature of the composite starch slurry was adjusted to 85° C. and stirred for 4 hours to obtain the modified binder.
7. The isostatically pressed graphite according to claim 6, characterized in that: The starch is soybean starch; The starch and water mixing mass ratio is 1:5; The high-speed beating speed is 4000r / min; The mixing ratio of the starch slurry and sodium alginate is 120 mL:5 g.
8. The method for preparing isostatically pressed graphite according to claim 1, characterized in that: The following steps are involved: S1: weighing the raw material components according to their weight parts: asphalt, modified coke powder, graphite powder, graphene, modified binder, and water; S2: adding modified coke powder, graphite powder, graphene and water to a mixer in sequence, stirring and mixing for 20 minutes, and then adding asphalt and modified binder respectively, and continuing to stir for 30 minutes to obtain a mixed slurry; S3: adding the mixed slurry into a mold, pressing, and then drying to obtain a blank; S4 adds the blank to the isostatic pressing die, adjusts the pressure to 300-330 MPa, maintains for 40 min, then adjusts the pressure to 450-460 MPa, continues to maintain for 30 min, and finally adjusts the pressure to 500-520 MPa, maintains for 25 min, to obtain a pressed material; S5 graphitizes the pressed material, cools it, and obtains isostatic graphite.
9. The method for preparing isostatically pressed graphite according to claim 8, characterized in that: The drying temperature is 200° C. and the drying time is 30 minutes.
10. The method for preparing isostatically pressed graphite according to claim 8, characterized in that: The graphitization treatment is carried out at 2500-2550° C. for 30-35 hours; The graphitization heating rate is 10°C / s.
Citation Information
Patent Citations
Preparation method of isotropic copper-based isostatic graphite composite material
CN108751992A
Preparation method of isostatic pressing graphite
CN117964366A
Compacted and calcined petroleum coke as well as production method and application thereof
CN118529718A
Manufacturing method for isotropic graphte article and high density isotropic graphte article manufactured by the method
KR1020180000915A